FRI0130 Fatigue, feeling blue and obesity, but not disease activity, predict whether patients with early inflammatory arthritis are able to walk considerable distances. (23rd January 2014) - Westhoff, G.; Callhoff, J.; Edelmann, E.; Zink, A.
Abstract : Background: Whether or not patients with inflammatory arthritis (IA) are still walking a considerable distance does not only depend on disease activity but also on many other chronic conditions that are frequently prevalent in middle aged individuals. Objectives: To assess the association between patients' characteristics at the beginning of rheumatologic care and the ability to walk 3 km one year thereafter. Methods: 603 patients participating in an observational study on early arthritis (<6 months; CAPEA 2010-2013) were followed with respect to the self-reported ability to walk 3 km after 12 months of rheumatologic care (with no or minor trouble vs. with great trouble or not at all). In a multivariate logistic regression analysis we included sex, education (compulsory, secondary, higher), smoking (never, past, currently), body mass index (BMI <25, 25-30, >30), 12 common chronic conditions (yes/no), RF and/or ACPA serology (negative, low-positive, high-positive), as well as the baseline arthritis parameters acute phase reactants (CRP and ESR normal vs. CRP or ESR abnormal), tender and swollen joint counts (T/SJC28 0-3, 4-10, >10), self-reported pain, morning stiffness and fatigue (VAS 0-3, 4-6, 7-10), and the first item of the Patient Health Questionnaire Depression scale (PHQ9):"Having little pleasure or interest in doing things" (not at all, on several days, more than half of the days). Results: Patients (66% female) were 56 ±14 years old and had symptom duration of 13 ±7 weeks. 59% were RF and/or ACPA positive, 66% fulfilled the new ACR-EULAR RA criteria at baseline and 88% took DMARDs at 12 months. At this point in time, 31% of the patients reported that they could not walk the distance of 3 km at all or only with great trouble. In multivariate logistic regression analysis, none of the arthritis activity measures or any of the considered cardiovascular, metabolic, pulmonary or degenerative diseases were associated with that outcome. Instead, failing to walk 3 km without considerable trouble was significantly associated with age, severe fatigue, feeling blue frequently, and obesity (Table ). Overall, 66% of the patients reported at least one of the three critical conditions. Conclusions: Whether or not patients with early arthritis are managing a 3 km walking distance without considerable trouble depends on health conditions that are usually not in the focus of routine rheumatologic care. Since two thirds of the IA patients had at least one of the conditions potentially hampering walking around, these conditions should be focussed in routine rheumatologic care. Disclosure of Interest: None Declared